2015
DOI: 10.2152/jmi.62.264
|View full text |Cite
|
Sign up to set email alerts
|

A case of thoracic esophageal cancer undergone esophagectomy after induction chemotherapy in a Jehovah's Witness

Abstract: We report the case of a 50-year-old female Jehovah's Witness with advanced esophageal cancer who underwent esophagectomy following induction chemotherapy. She visited our hospital complaining of dysphagia and was diagnosed of advanced esophageal cancer by upper endoscopy. She refused allogeneic transfusion. Induction chemotherapy was performed. Severe anemia occurred as an adverse event. A subtotal esophagectomy was performed after her anemia improved. During the surgery, a large volume of replacement fluid wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Indeed, accumulating evidence proved that excess blood transfusion during surgery might not improve but even aggravated the prognosis and increased post-operative complications, especially in curative surgery for malignancies (Meng et al, 2013;Aquina et al, 2015;Diaz-Cambronero et al, 2015;Li et al, 2015;Prescott et al, 2015). Hence, oncologic surgeries without blood transfusion were developed without increased post-operative complications by means of replacement fluid administration, autologous blood infusion, parenteral iron supplement and the use of erythropoietic-stimulating agents (Lee et al, 2014;Borstlap et al, 2015;Diaz-Cambronero et al, 2015;Inoue et al, 2015). Recently, it was reported that such novel methods for blood preservation could be practical in oncologic surgeries, particularly for the selected populations such as patients with uncommon blood types or multiple RBC allo-antibodies, as well as Jehovah's Witnesses.…”
Section: (B) (A)mentioning
confidence: 99%
“…Indeed, accumulating evidence proved that excess blood transfusion during surgery might not improve but even aggravated the prognosis and increased post-operative complications, especially in curative surgery for malignancies (Meng et al, 2013;Aquina et al, 2015;Diaz-Cambronero et al, 2015;Li et al, 2015;Prescott et al, 2015). Hence, oncologic surgeries without blood transfusion were developed without increased post-operative complications by means of replacement fluid administration, autologous blood infusion, parenteral iron supplement and the use of erythropoietic-stimulating agents (Lee et al, 2014;Borstlap et al, 2015;Diaz-Cambronero et al, 2015;Inoue et al, 2015). Recently, it was reported that such novel methods for blood preservation could be practical in oncologic surgeries, particularly for the selected populations such as patients with uncommon blood types or multiple RBC allo-antibodies, as well as Jehovah's Witnesses.…”
Section: (B) (A)mentioning
confidence: 99%
“…However, detailed treatment plans have been entrusted to each institution, and invasive treatment for JWs remains a medical and ethical issue. Some reports have described surgical treatment for JWs [1,2,[7][8][9]. Although case reports have described abdominal surgery, cardiovascular surgery, and liver or lung transplantation, very few have mentioned pulmonary surgery, especially cases of lung cancer [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have described surgical treatment for JWs [ 1 , 2 , 7 9 ]. Although case reports have described abdominal surgery, cardiovascular surgery, and liver or lung transplantation, very few have mentioned pulmonary surgery, especially cases of lung cancer [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation